Regional Features of Energy Resources Extraction in Eastern Siberia and the Far East - Abramov, Ruslan A.; Tronin, Sergey A.; Brovkin, Alexander V.; Pak, Khin Cho (International Journal of Energy Economics and Policy, 2018)
The role and importance of the energy sector in the development of the Russian economy is currently difficult to overestimate, because among all sectors of the economy it performs a supporting function and is of fundamental importance. Therefore, the main goal of the work is to analyze the characteristics of oil production in Siberia and other regions of Russia. The authors analyzed the global volumes of oil production. It is established that Russia is the top five in oil production. It is established that the production of condensate in the Yamal-Nenets Autonomous District may increase to 21.2 million tons in 2030, ethane – 13 million tons of propane – 8.6 million tons, butane – 4.9 million tons. Also, the authors analyzed the operational equipment breakdowns. Keywords: energy sector, economic policy, resources, General model, refined products. JEL Classifications: Q400, Q430, Q480.